Evaluation of Dual-port versus Single-port Tissue Expanders in Postmastectomy Breast Reconstruction. Issue 7 (15th July 2021) - Parmeshwar, Nisha; Piper, Merisa; Viner, Jennifer; Foster, Robert; Kim, Esther A.
Abstract : Background: Immediate tissue expander placement in postmastectomy breast reconstruction can be complicated by seroma or infection, requiring further imaging studies or interventions. This study compares dual-port tissue expanders, with both an aspiration and expansion port, with single-port expanders in terms of postoperative complications and further interventions. Methods: Patients with immediate tissue expander placement from March 2019 to March 2020 were reviewed. Complications included seroma, infection, hematoma, necrosis, and malposition of the expander. Further intervention included aspiration, ultrasound imaging, interventional radiology (IR) drainage, or return to operating room. Results: In total, 128 dual-port expanders were compared with 125 single-port expanders. Patients with single-port expanders were younger ( P = 0.022) and of lower BMI ( P = 0.01). There were no significant differences in key complications between these groups. In multivariate analysis, single-port expanders had a 3.4× higher odds of postoperative ultrasound imaging when controlling for texture, placement, and age ( P = 0.01). Mean time to IR drain placement in the dual-port group was approximately 30 days after placement in single port (51.1 versus 21.4 days, P = 0.013). Thirty-four percent of dual-port expanders had at least one aspiration in clinic performed by plastic surgery, versus 2% of single port that required ultrasound-guided aspiration ( P < 0.001). Conclusions: There were no differences in key postoperative complications between the two expander cohorts. Dual-port expanders significantly reduced postoperative ultrasound imaging, and delayed IR drain placement. The added convenience of clinic aspirations likely reduced costs related to utilization of resources from other departments.